2011
DOI: 10.1596/1813-9450-5669
|View full text |Cite
|
Sign up to set email alerts
|

Does Cash for School Influence Young Women's Behavior in the Longer Term? Evidence from Pakistan

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
0
12
0
3
Order By: Relevance
“…RMG is the main source of export for the last 25 years, and this sector employs more than 3 billion people in Bangladesh of whom 90% are poor and underprivileged women (Ahamed, 2014). However, job satisfaction of RMG workers in Bangladesh are decreasing at present time due to improper work practices that include insufficient salary, discrimination, unhealthy work environment, frequent work accidents and hazards (Aslam et al, 2011;Adbin, 2008;Berik & Rodger, 2008;Hossan et al, 2012a;Hossan et al, 2012b). As a result, dissatisfied RMG workers in Bangladesh are creating unrest and raising voice in recent time.…”
Section: Introductionmentioning
confidence: 99%
“…RMG is the main source of export for the last 25 years, and this sector employs more than 3 billion people in Bangladesh of whom 90% are poor and underprivileged women (Ahamed, 2014). However, job satisfaction of RMG workers in Bangladesh are decreasing at present time due to improper work practices that include insufficient salary, discrimination, unhealthy work environment, frequent work accidents and hazards (Aslam et al, 2011;Adbin, 2008;Berik & Rodger, 2008;Hossan et al, 2012a;Hossan et al, 2012b). As a result, dissatisfied RMG workers in Bangladesh are creating unrest and raising voice in recent time.…”
Section: Introductionmentioning
confidence: 99%
“…The study reports a strong positive influence of female school stipend programs on female school enrollment. Chaudhury and Parajuli (2007), Alam et al (2011), and Ahmed and Zeshan (2014), also found a similar relationship between school stipend and student enrollment especially in the case of female school enrollment. Cash transfers help to ease off the financial burden on the parents and they find it easier to send their kids especially girls to school.…”
Section: Discussionmentioning
confidence: 61%
“…Of these, eight studies examining seven programs assessed the magnitude of the program effect by exposure level in the study results (Table 3). Overall, seven of the eight studies found evidence that longer exposure was associated with greater benefit [41][42][43][44][45][46][47][48]. Six of these seven were medium-quality studies, with results based on better outcomes on a range of outcome indicators, but all showed greater benefit on indicators of behavior change or impact; one was a low-quality study with results based on school enrollment.…”
Section: Implementation Science Findingsmentioning
confidence: 99%
“…Two studies tested whether program results varied by exposure level using statistical tests of difference and both found evidence that longer exposure was associated with greater benefit [42,46]. Additionally, two of the included studies assessed the magnitude of program effect(s) by exposure level over multiple followup assessments [44,46].…”
Section: Implementation Science Findingsmentioning
confidence: 99%